The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1152/ajpheart.00574.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic sensing using subcutaneous photoplethysmography

Abstract: Turcott RG, Pavek TJ. Hemodynamic sensing using subcutaneous photoplethysmography. Am J Physiol Heart Circ Physiol 295: H2560 -H2572, 2008. First published October 10, 2008 doi:10.1152/ajpheart.00574.2008.-Pacemakers and implantable defibrillators presently operate without access to hemodynamic information. If available, such data would allow tailoring of delivered therapy according to perfusion status, optimization of device function, and enhancement of disease monitoring and management. A candidate method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…9,1921,2426,30,3640 Although each has a rationale that is mechanistically plausible, consideration of the neurohormonal derangements of heart failure and the therapeutic interventions that have been successful lead us to view SV and its surrogates as parameters that when optimized are most likely to translate into clinical benefit. Specifically, it is now well established that ameliorating the effects of sympathetic tone in these patients leads to improved clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…9,1921,2426,30,3640 Although each has a rationale that is mechanistically plausible, consideration of the neurohormonal derangements of heart failure and the therapeutic interventions that have been successful lead us to view SV and its surrogates as parameters that when optimized are most likely to translate into clinical benefit. Specifically, it is now well established that ameliorating the effects of sympathetic tone in these patients leads to improved clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…61 The technology, which is commonly used in noninvasive pulse oximetry, uses light for noninvasive assessment of microvascular blood volume. In a proof-of-concept canine study, a photoplethysmography sensor was implanted subcutaneously, and waveforms showed an excellent correlation with aortic pressure during rapid ventricular pacing or changes in atrioventricular delay.…”
Section: Future Directionsmentioning
confidence: 99%
“…In a proof-of-concept canine study, a photoplethysmography sensor was implanted subcutaneously, and waveforms showed an excellent correlation with aortic pressure during rapid ventricular pacing or changes in atrioventricular delay. 61 It was proposed that inclusion of this sensor in a pulse generator may allow measurement of a surrogate marker for acute changes in arterial pressure. Furthermore, appropriately filtered photoplethysmography data may provide information on venous capillary flow and respiration and may be used to aid management of sleep-disordered breathing.…”
Section: Future Directionsmentioning
confidence: 99%
“…It is a sensing technology that has many of the features of an ideal hemodynamic sensor. Notably, it responds in a direct proportion to acute changes in systemic blood pressure 13 . The present study quantitatively evaluated the ability of subcutaneous PPG to discriminate hemodynamically unstable arrhythmias from stable arrhythmias that were simulated by rapid pacing in an acute canine preparation.…”
Section: Introductionmentioning
confidence: 99%